Impact Analysis of Minimum Wages, Investments and Inflation on Labor Absorption in the Manufacturing Industry in Indonesia - Rini, Esa Fajar; Septriani, Septriani (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2025)
The Purpose of this research is to analyze the influence of investment, minimum wages, and inflation on labor absorption in the manufacturing industry in Indonesia. The analytical tool used is multiple linear regression using time series data for the period 1991-2021, by using secondary data sourced from the Statistics Indonesia (BPS). Based on the results of the study, the results were obtained that partially, each variable minimum wages and investments have a significant positive impact on the absorption of labor in the manufacturing industry in Indonesia. The inflation variable has a significant negative impact on labor absorptions in processing industries in Indonesia. While simultaneously the minimum wage, investment, and inflation have an influence on the consumption of labor in the manufacturing industry. With R-squared at 0.92. Based on the results of this study, related to the problem of low contribution of the industrial sector in job absorption, it can be overcome by increasing investment and minimum wage in the industrial sector, as well as controlling inflation. This is important to predict the high unemployment rate and also increase Indonesia’s economic growth. However, in implementing the minimum wage policy, the government must still consider the ability to pay from the industrial sector. Then, the government actively participates in making fiscal and monetary policies that can stimulate the growth of the investment climate in the industrial sector. In addition, the government must also always maintain price stability, because this has a significant impact on the sustainability of the industrial sector.